Broth Characteristics of Broiler Chicken, Free-Range Chicken, and IPB D1 Chicken - M. F. Ridwan; C. Budiman; Z. Wulandari (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
Broth is a product made from beef or poultry by cooking ingredients rich in protein and water, with or without the addition of spices, vegetable fat and sodium chloride. This study aims to determine the physicochemical properties including crude protein, ash, fat, carbohydrates, water activity, and pH as well as organoleptic tests of three types of broth from different chicken meat, namely broiler, free-range chicken, and IPB-D1 chicken. An organoleptic test was performed using quantitative descriptive analysis (QDA). The results showed that the different types of chicken strains did not significantly affect the value of water content, ash content, protein content, pH value and viscosity. The descriptive quantitative analysis (QDA) test followed by the ANOVA test showed that the difference in the types of chicken strains has no significant effect on the sensory attributes of chicken taste, salty taste, tastelessness, bitter aftertaste, and carnation aftertaste. Chicken broth made from native chicken gave the best characteristicresults for the analysis of physicochemical and organoleptic properties.